UNIVERSALITY AND PARTICULARITY: THE CAUSE FOR INCONSISTENCY IN ACQUISITION OF KNOWLEDGE - Joseph Munyoki Mwinzi (Universitas PGRI Madiun, 2022)
A philosophical cause of universality and relevance in the acquisition of knowledge is annexed by the reality of inconsistency in the academic stadium. In essence, knowledge and by extension education is considered by universality as an essential substratum. It follows necessarily that knowledge which is an abstract reality is perceived to be universal, with minimal reference to particularity as the source of knowledge. Accordingly, when all variables are held constant, the acquisition of knowledge should be a form of a linear track which attracts the purview of particularity. This is why universality in the acquisition of knowledge is volatile due to inconsistencies caused by its nature in relation to acquisition of such knowledge in education theory and practice. Therefrom, this article delineates the cause-effect relationship of such discrepancy by emphasizing that there occurs extrication between the knower, the known, and the process of knowing. In this case, the knower is the recipient of knowledge, the known is the subject of knowledge, and the process of knowing is the modality of dispensing such knowledge.